The Impact of Sun Protection Program on the Sun Protection Behavior of Adolescents - ERGÜN, AYŞE (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Background: The incidence of skin cancers is steadily increasing. In particular, because children and adolescents tend to be outdoors during the hours of most intensive sunlight, schools play an important role in establishing sun protection behavior among students. Purpose: The aim of this research was to investigate the effect of a Sun Protection Program (SPP) on the sun protection behavior of Turkish adolescents. Methods: This study was designed as pre-/posttest control group semi-experimental research. The research was carried out with 147 adolescents from years 12-15 in two schools. One of the schools was randomly designated as the intervention group of students and the other represented the control group. The study samples included 76 students in the intervention group and 71 students in the control group. Covariants were calculated in the pre-test scores and covariance analysis performed to evaluate the impact of the intervention on both groups. The SPP formed the basis for the program and consisted of 6 posters, a 12-page student handbook, 4 puzzles, educational videos, and a UV-sensitive Frisbee game. Results: The intervention group's sunscreen use and sun avoidance stages, and self-efficacy mean scores was significantly higher than those of the control group after the implementation of the SPP (p<.001). In addition, the increase in the scores on the posttest as compared to the baseline in the sunscreen stage as well as in the pros scores was found to be significant in the intervention group but not in the control group (p<.05). Conclusion: The study showed that a school-based SPP was effective in the short term in achieving progress in the Transtheoretical Model (TTM) sunscreen use stages, perceiving pros and in sun avoidance, sunscreen and hat use self-efficacy, meaning that the program may be used in schools to increase sun protection behavior. School-based, nurse-led, short-term studies encompassing group interventions are successful in developing sun protection attitudes and will be useful in the future in the context of school nursing activities.
Keywords: Adolescent; Skin cancer prevention; Sun exposure; Sun protection; Transtheoretical model; PREVENT SKIN-CANCER; RANDOMIZED-TRIAL; MULTICOMPONENT INTERVENTION; DECISIONAL BALANCE; EXPOSURE; MOTIVATION; CHILDHOOD; MELANOMA; CHILDREN; RISK